PERLINDUNGAN HUKUM TERHADAP EKSPLOITASI ANAK JALANAN MENURUT PERATURAN DAERAH KOTA SAMARINDA NO. 16 TAHUN 2002 TENTANG PENERTIBAN DAN PENANGGULANGAN PENGEMIS, ANAK JALANAN DAN GELANDANGAN DALAM WILAYAH KOTA SAMARINDA - Pahrul Raji (Universitas 17 Agustus 1945 Samarinda, 2015)
ABSTRACTChildren are a gift of God Almighty as the future generation that is still in physical and mental development. Children who should be in the neighborhood and the school during school hours learning activities at night in the house but was spent on the road, both because of the willingness themselves, their parents or exploited by unscrupulous irresponsible. In order to ensure legal protection against street children local governments Samarinda City has passed a law Samarinda City at No. 16 of 2002 on Control and Prevention Beggars, Street Children and Homeless In Urban Area Samarinda, but until now the street children is still difficult to protect the rights Street children. Based on this background, the authors take the title